[Disulfanediylbis(ferrocenylthiophosphinato)-κ2O,O]titanocene tetrahydrofuran trisolvate - Mehmet Karakus; J. Derek Woollins; Peter Lönnecke; Evamarie Hey-Hawkins (Acta Crystallographica Section E, 2012)
The title compound, [Fe2Ti(C5H5)4)(C10H8O2P2S4)]·3C4H8O, contains a central seven-membered TiO2P2S2 ring with a very similar geometry compared to the derivative showing anisyl instead of ferrocenyl substituents, the Ti—O distance being marginally longer for the anisyl derivative. Two tetrahydrofuran solvent molecules are each disordered on a twofold axis.